Tasks in Information Modelling as Development Means of Schoolchildren's Creative Abilities. (5th December 2015) - Shtepa, Yulia; Bazhenov, Ruslan; Smirnova, Anna; Filippova, Galina; Vashakidze, Natella
Abstract: The article substantiates the need to intensify practice-oriented teaching of information modelling. Commonality of information modelling tasks and creative tasks is disclosed; the role of such tasks in developing creative abilities of senior pupils in teaching informatics is described. The specificity of the task statement allows to classify information modelling tasks into the tasks with insufficient, redundant, contradictory or null information and depending on the character of the purpose they may be of prognostication, optimization, research, reviewing and other types. Experimental work in teaching pupils to solve information modelling tasks within the school course of informatics is described. 148 schoolchildren were involved in the forming stage of the experiment. It has been proved that teaching pupils to solve information modelling problems leads to positive changes in the development level of flexibility, fluency, and originality of thinking as components of creative abilities.